Pemanfaatan Urea sebagai Sumber Nitrogen pada Biosolubisasi Batubara oleh Trichoderma sp. - Mulyawati, Novi; Pikoli, Megga Ratnasari; Sugoro, Irawan; Aditiawati, Pingkan (Al-Kauniyah: Jurnal Biologi, 2013)
Lignite coal was found abundant in Indonesia, but usage for this type of coal was still relatively low. Economic value of coal increases when it is solubilized. Biosolubilization of coal by utilize of microbes produces compounds equivalent to petroleum. In this research, effect of urea on lignite biosolubilization by Trichoderma sp. was examined. Method of this research consisted of spore inoculum preparation, biosolubilization lignite coal with a variety of treatment that consists of treatment A (MSS + sucroseÂ  1% + coal 5% + urea), and treatment B (MSS + sucroseÂ  1% + coal 5%). Results showed that the addition of urea supported lignit coal biosolubilization by Trichoderma sp. based on increase in medium pH, concentration of phenolic and conjugated aromatic compounds, and activity of extracellular enzyme. In addition, result of product characterization using GCMS revealed compounds equivalent to 13,60%, 26,20% and 90,8% respectively for gasoline, kerosene and diesel components. Those confirmed that urea can be used as an alternative nitrogen source to support Trichoderma sp. in lignit biosolubilization producing petroleum compounds.